Efektivitas Bimbingan Kelompok Dengan Teknik Problem Solving Terhadap Kemampuan Berpikir Kritis Siswa Kelas XI MIPA 3 SMA Negeri Colomadu Tahun Pelajaran 2021/2022. - Zulfa, Anisah Nasih (Program Studi Bimbingan dan Konseling FKIP Universitas Slamet Riyadi, 2023)
This study aims to determine the effectiveness of Group Guidance with Problem Solving Techniques on the Critical Thinking Ability of Class XI MIPA 3 SMA Negeri Colomadu in the Academic Year 2021/2022. This research is a quantitative experimental research with Pre Experimental Design One Group Pretest-Posttest Design research design. The population in this study were all students of class XI MIPA 3 SMA Negeri Colomadu in the academic year 2021/2022, totaling 33 people. The research sample uses a saturated sample, where the population is also used as a sample. Data collection techniques using questionnaires and documentation. The data analysis technique used is t-test. Based on the results of data analysis, the t-count value is 16.593. Furthermore, the t-count value was consulted with the t-table at d.b=N-1=32 and the significance levels of 5% and 1% were 2.037 and 2.738, thus the results of data analysis obtained that t-count was greater than t-table or 2.738<16,593>2,037. Thus Ho which states